The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/1687814016664703
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical variations in white and gray matter affect the biomechanics of spinal cord injuries more than the arachnoid space

Abstract: Traumatic spinal cord contusions lead to loss of quality of life, but their pathomechanisms are not fully understood. Previous studies have underlined the contribution of the cerebrospinal fluid in spinal cord protection. However, it remains unclear how important the contribution of the cerebrospinal fluid is relative to other factors such as the white/ gray matter ratio. A finite element model of the spinal cord and surrounding morphologic features was used to investigate the spinal cord contusion mechanisms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Mechanical anisotropy in the human spinal cord has been previously linked to the microstructural properties of anisotropy within white matter tissue [46,47]. An improved understanding of the mechanical anisotropy that exists within the spinal cord is important for generating more accurate in silico models of traumatic spinal cord injury [48].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical anisotropy in the human spinal cord has been previously linked to the microstructural properties of anisotropy within white matter tissue [46,47]. An improved understanding of the mechanical anisotropy that exists within the spinal cord is important for generating more accurate in silico models of traumatic spinal cord injury [48].…”
Section: Discussionmentioning
confidence: 99%
“…This shows that regardless of the assumptions made on the WM and GM material properties, it is possible to simulate the global mechanical behavior of the spinal cord. The three sets were chosen in view of the available data and have all been used in spinal cord FE model investigating injury mechanisms [12,13,18,[32][33][34]. This study demonstrated the strong impact of the choice of material properties on the local mechanical behavior throughout the spinal cord.…”
Section: Plos Onementioning
confidence: 99%
“…Yet, the mouse spinal cord and its surrounding structures have distinctive morphological and structural features, including its size and its proportion of white matter (WM) and gray matter (GM) [16] or the absence of subarachnoid space [17]. These morphological features have been shown to strongly affect the biomechanics of SCI in numerical models [18]. Thus, accurate representation of the mouse spinal cord structure is required to properly correlate numerical results (local mechanical stresses and strains) with experimental results (local tissue damage).…”
Section: Introductionmentioning
confidence: 99%
“…However, this does not challenge our conclusions since high stress and strain appeared at less than 30of extension, which is a normal range of extension for the elderly, according to Muhle et al (1998). Thirdly, the mechanical behaviour of white and grey matter was defined by isotropic strain rate-dependent tabulated laws derived from experiments reported in the literature (Fradet et al, 2016).…”
Section: Discussionmentioning
confidence: 99%